THE ROLE OF BRAND IMAGE, CELEBRITY ENDORSER, PRODUCT QUALITY IN PURCHASING DECISIONS FOR MS GLOW SKIN CARE PRODUCTS IN SIDOARJO - Khoirun Nisa Ashada; Dewi Komala Sari (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to analyze the influence of brand image, celebrity endorsers, and product quality on purchasing decisions for MS Glow skincare products in Sidoarjo City. Method: A quantitative research approach was applied using purposive sampling, with a total of 97 respondents who are consumers of MS Glow products. Data were collected through questionnaires and analyzed using multiple linear regression and hypothesis testing. The independent variables include brand image, celebrity endorser, and product quality, while the dependent variable is purchasing decision. Results: The findings indicate that brand image, celebrity endorser, and product quality each have a positive and significant effect on purchasing decisions for MS Glow skincare products in Sidoarjo. These results suggest that consumer perceptions of brand reputation, influencer credibility, and product performance play a key role in shaping purchasing behavior. Novelty: This study contributes to marketing literature by providing empirical evidence on how brand communication and perceived product quality jointly influence consumer decision-making in the competitive skincare industry.